A survey on the use of remote consultation for people with intellectual disability: The experience of community intellectual disability teams. Issue 1 (2nd January 2023) - Nicholson, Laura; Sharma, Sudhakar; Andrews, Sarah; Farquharson, Alistair; Welsh, H.
ABSTRACT: Background: Since COVID-19, remote consultation (by telephone and video) has become widespread. This study investigated the experience of using remote consultation in Specialist Intellectual Disability Community services. Method: A total of 126 health staff working across eight Specialist Intellectual Disability Community teams in the NHS Health Board of Greater Glasgow and Clyde were asked to complete a short Likert-scale survey about remote consultation. Results: There were 61 (48%) respondents from a range of disciplines. Overall, respondents were positive about remote consultation but found it was often inadequate to complete a full patient assessment. Moving forwards, respondents wanted around 60% of all consultations to remain face-to-face. It was significantly more difficult to engage and communicate with patients with more severe levels of disability. Conclusions: Remote consultation has been successful, but there is still a need for face-to-face assessment in intellectual disability services, particularly when working with people with more severe levels of disability.